2018
DOI: 10.1162/glep_a_00458
|View full text |Cite
|
Sign up to set email alerts
|

Sustainably Sourced Junk Food? Big Food and the Challenge of Sustainable Diets

Abstract: Sustainable diets are an increasingly debated policy concept to address many of the environmental, social, and economic issues in the food system. The role of ultraprocessed foods in sustainable diets has received less attention than meat, dairy, and eggs but is deserving of examination given the high environmental impacts and negative health outcomes resulting from consumption of these foods. Big Food companies that make ultraprocessed foods have focused their attention on sustainable sourcing as a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…This included consideration of animal welfare, social, and environmental impacts. Analysis of global food manufacturers found that such sustainable sourcing initiatives overlooked the most important factor, that is how to achieve healthy and sustainable diets [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…This included consideration of animal welfare, social, and environmental impacts. Analysis of global food manufacturers found that such sustainable sourcing initiatives overlooked the most important factor, that is how to achieve healthy and sustainable diets [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst sustainable sourcing initiatives can contribute to improving some aspects of the food system, they do not address the bigger issue of encouraging healthy and sustainable population diets [126]. The supermarket CSR policies did not refer to healthy and sustainable diets, which may be because there is not one commonly agreed upon definition [75] or approach to describing the level of sustainability of a diet [127].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years the importance of sustainability in agrifood chains is widely discussed in scientific literature as well as in public (13). In these discussions, sustainability is very often reduced solely to ecological factors (4).…”
Section: Definition Of Nutritional Sustainabilitymentioning
confidence: 99%